The Analysis of Politeness Principles on Literature and Language Teaching in Class Presentation - Barik, Alvi Rizqi (Journal of Literature, Linguistics, & Cultural Studies, 2023)
ABSTRACT This research examined the deviation of maxims of politeness which produced by English lecturers and students of UIN Maulana Malik Ibrahim Malang in class presentation activity. Qualitative research used in this research to collect the data to explore the deviations produced during the activity. The researcher employed an observation to learn how the deviation occurred based on the fact and reality that happened during the activity. The data of the research were taken from three classes including History of English Literature, History of American Literature and English Language Teaching (ELT). The participants included in the research were three lecturers and 240 students of the fifth semester. The analysis of the data used the theory proposed by Leech (1983) that classified six maxims of politeness principles including Tact maxim, Generosity maxim, Approbation maxim, Modesty maxim, Agreement maxim and Sympathy maxim. This research found that there were 18 utterances produced by English lecturers and student of UIN Maulana Malik Ibrahim Malang in class presentation activity which deviated 3 maxims of politeness principles including: Tact maxim, Generosity maxim and Agreement maxim. It was expected that this research could give new insight for the readers to pay attention on the use of politeness principles. Thus, the deviation of maxims of politeness principles could be minimized and the conversation could run smoothly Keywords: Class presentation, Deviation, Politeness principles.